Thrombotic Thrombocytopenic Purpura with Mixed Connective Tissue Disease –Non-immune Hemolytic Anemia with Autoimmune Disease - Rare Case Report - Momin, Majed Abdul Basit; Prusty, B Saroj Kumar; Reddy, Amitha (Journal of Bangladesh College of Physicians and Surgeons, 2019)
TTP (Thrombotic Thrombocytopenic purpura) is a nonimmune, microangiopathic hemolytic anemia (MAHA), associated with thrombocytopenia, fever, neurologic or renal dysfunction. Mixed connective tissue disease (MCTD) is not a specific disorder and identified serologically by high titers of of antibodies to RNP. Coexistence of TTP with asymptomatic MCTD is rare encounter. We describe here a rare case of secondary TTP in a 42 year, old female presenting as menorrhagia for seven days, severe headache and one episode of seizure. This case emphasizes the early diagnosis of TTP and its association with underlying condition for proper management and to avoid fatal outcome. KeyWords: Microangiopathic hemolytic anemia (MAHA); Thrombotic Thrombocytopenic purpura( TTP); hemolytic uremic syndrome(HUS); Mixed connective tissue disease(MCTD); U1-Ribonucleoprotein (RNP); Antineuclear antibody(ANA); A disintegrin and metalloproteinase with a thrombospondin type 1 motif,member 13(ADAMTS 13) J Bangladesh Coll Phys Surg 2020; 38(1): 46-48